PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA LET’S READ TERHADAP MINAT BELAJAR IPA SISWA KELAS IV SDN 3 BILATO KABUPATEN GORONTALO - Diasamo, Ridhayanti; Kudus, Kudus; Arif, Rifda Mardian (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this research is to determine the effect of the Problem Based Learning (PBL) model assisted by the Let’s Read media on the learning interest in science of fourth-grade students at SDN 3 Bilato, Gorontalo Regency. This study uses a quantitative approach with a pre-experimental research design employing a one group pre-test and post-test design. The research sample comprises all fourth-grade students at SD Negeri 3 Bilato. This research utilizes an instrument in the form of a learning interest questionnaire that has been tested and deemed valid and reliable. The results of the classical assumption test indicate that the research data is normally distributed and homogeneous. The results of this study found a significant increase in students' learning interest. The average score of students' learning interest increased from 39.52 (pre-test) to 71.20 (post-test). The results of the Independent T-test showed a Sig. (2-tailed) value of 0.000, which is less than 0.05 (p<0.05), proving that there is a significant effect of the implementation of the PBL model assisted by the Let’s Read media on students' interest in learning science. In addition, the N-Gain Score test result of 0.79 (79%) indicates a high increase in learning interest, affirming that the PBL model with the Let’s Read media is effective for use in learning. This is also supported by the increase in student learning outcomes before and after the treatment was conducted in the research class.